Effectiveness of Homemade Herbal Powder in Reducing Blood Glucose Levels in Diabetes Mellitus Mice - Shinta Mayasari; Laila Camelia; Hartalina Mufidah; Alwiya Kinanti; Neny Poerwahyuningrum (LPPM Universitas dr. Soebandi, 2026)
ABSTRACT Diabetes Mellitus is a disease characterized by the inability of the pancreas gland to produce insulin, which can cause an increase in glucose levels in the blood. Treatment for this disease can be said to be quite expensive and requires long treatment. Noni, red ginger, black cumin, Chinese petai seeds and cardamom contain antioxidant compounds that can reduce blood glucose levels. These natural ingredients can be made into a drink in the form of homemade herbal powder can reduce glucose levels in the blood. This study aims to determine the effectiveness of homemade herbal powder on blood glucose levels. The method used in this research is an experimental method with a pre-post design. This study was divided into 5 treatment groups, namely negative control group, positive control, treatment group 1 with a dose of 400 mg/kg BB, treatment group 2 with a dose of 600 mg/kg BB and treatment group 3 with a dose of 800 mg/kg BB. The sample size was determined using the Federer formula, amounting to 5 individuals in each treatment. The results of analysis using Paired sample T-test showed a p-value of 0.000 or sig value <0.05, which means that homemade herbal powder at doses of 400, 600 and 800 mg/kg BW can reduce blood glucose levels. The compounds contained in herbal plants that function as antioxidants can help absorb glucose and help pancreatic beta cells produce insulin. Homemade herbal powder can reduce blood glucose levels and the highest average reduction was found at a dose of 800 mg/kg BB. Keywords: Diabetes mellitus; Blood Glucose; Herbal Powder